Experimental analysis of the scaled DTU10MW TLP floating wind turbine with different control strategies. (August 2020) - Madsen, F.J.; Nielsen, T.R.L.; Kim, T.; Bredmose, H.; Pegalajar-Jurado, A.; Mikkelsen, R.F.; Lomholt, A.K.; Borg, M.; Mirzaei, M.; Shin, P.
Abstract: The experimental testing of a Tension Leg Platform (TLP) floating wind turbine at 1:60 scale in wind and waves with a pitch-regulated 10 MW wind turbine is presented. The floating wind turbine was tested with three different control configurations: two closed-loop controllers and one open-loop controller. The experimental setup and program is described in this paper, and system identification and the responses of the floater to hydrodynamic loading are analysed and compared for the different control strategies. It was observed that negative aerodynamic damping for the onshore controller resulted in high oscillations in blade pitch, yielding an increased response in surge for all wave types. It was also observed that the surge motion governed the mooring line tensions, thus the onshore controller yielded the highest tensions in the front mooring line. Further the shutdown cases of the offshore controller led to larger surge displacement when the shutdown was initialized right before the wave impact. Highlights: A scaled TLP floating wind turbine model test with pitch control has been performed. Various environmental conditions have been considered with and without wind. Different control strategies (onshore, offshore, and fixed) are investigated. It reveals that the onshore controller induced high oscillations in blade pitch. Emergency shutdown condition with various focused wave cases is investigated.